EVALUASI PERHITUNGAN HARGA POKOK PRODUKSI TERHADAP UMKM BEPPA JANDA DESA TELUK KABBA MENGGUNAKAN METODE FULL COSTING - Erni, Erni; Kadafi, Muhammad; Aprilia, Juwita (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2024)
The purpose of this study is to calculate the cost of production of UMKM Beppa Janda in Teluk Kabba Village, and calculate the selling price of Beppa Janda at UMKM Beppa Janda in Teluk Kabba Village. Calculating the difference between the calculation of the cost of production before and after the research on the UMKM Beppa Janda Teluk Kabba Village using the full costing method. The data collection techniques used in this study were observation, interviews and documentation. The data analysis technique used in the study to answer the formulation of this problem was descriptive analysis. The results of this study indicate that there are differences in the calculation of the cost of goods manufactured by the company with the full costing method. The cost of production of Beppa Janda using the company's calculation is Rp. 802.6 and for the Full Costing method that is Rp. 811.3. The calculation difference is Rp. 8.7. This is influenced by the cost of raw materials, factory overhead costs, both variable and fixed